Operando monitoring of mechanisms and deactivation of molecular catalysts. Issue 5 (25th February 2022) - Köhnke, Katrin; Wessel, Niklas; Esteban, Jesús; Jin, Jing; Vorholt, Andreas J.; Leitner, Walter
Abstract : The review presents spectroscopic and mathematical tools to perform operando investigations of mechanisms and deactivation pathways in homogeneous catalysis. Their potential is shown in two case studies, hydroformylation and asymmetric hydrogenation. Abstract : Observing and understanding the phenomena associated with the reaction mechanisms and catalyst deactivation in molecular catalysis is a very challenging task in green chemistry. This knowledge is crucial for applying and scaling catalyzed reactions as well as preventing misproduction at a very early point. Over the years, experimental arrangements have evolved towards analysis of catalysts and reaction products in the so-called operando setups. This contribution reflects on the potential of operando studies to elucidate reaction and deactivation mechanisms in homogeneous catalysis as well as the outstanding opportunities that arise from the application of operando experimental setups. Such setups mostly rely on spectroscopic analysis, optionally coupled with chromatographic techniques that monitor the reaction system. This in turn means that not only the evolution of the reaction substrates and products can be monitored, but also changes of the molecular catalyst species that may affect the catalytic performance. Therefore, this review focusses on techniques to monitor the catalyst under real conditions. In this review, different spectroscopic techniques relevant for monitoring molecular transition metal catalysts in solution are covered, followed by numerical methods used in the chemometrics literature to undertake the challenge of untangling the complex raw signals and allocating them to individual chemical species. Finally, two exemplary case studies of industrially relevant chemical reactions are presented, namely the hydroformylation and the asymmetric hydrogenation. These examples illustrate the significance of the application of both the experimental setups as well as data processing and signal resolution to have an insight into the deactivation of catalytic systems. The operando approach shows high potential for the increased use in future research to develop stable and more selective catalysts which can be applied in greener processes.